Islamic leadership and transparency practices in takaful organizations - Raja Rizal Iskandar Raja Hisham; Mohd Rizal Palil; Wan Aishah Wan Mohd Nowalid; Muhamad Rahimi Ramli (Penerbit Universiti Kebangsaan Malaysia, 2019)
Takaful industry is faced with the issue of ineffective governance practices although it continues to excel financially at a rapid growth rate. Previous studies have started to address the importance of leadership to improve the level of transparency practices in Takaful organizations. However, little is made known on how the role of Islamic leadership would fit into the equation. Hence, the current study aims to examine the relationship between Islamic leadership and transparency. From the literature, Islamic leadership was grounded by the servant leadership approach which consists of five domains, namely altruistic calling, emotional healing, wisdom, persuasive mapping, and organizational stewardship. A self-administered questionnaire was employed to collect the data from employees of licensed Takaful operators in Malaysia. 208 usable data were analyzed using SmartPLS software to test the hypotheses of the study. The findings revealed that altruistic calling and persuasive mapping were significant factors influencing transparency, and the other three variables have no significant effect towards transparency. Emotional healing was found to be the most underperforming factor that needs to be further improved by managers. In addition, this study provides discussion, implications, limitation, and suggestion for future study.